Complete characterization of extreme quantum observables in infinite dimensions - Pellonpaa JP (IOP PUBLISHING LTD, 2022)
We give a complete characterization for extreme quantum observables, i.e. for normalized positive operator valued measures (POVMs) which are extremals in the convex set of all POVMs. The characterization is valid both in discrete and continuous cases, and also in the case of an infinite-dimensional Hilbert space. We show that sharp POVMs are pre-processing clean, i.e. they cannot be irreversibly connected to other POVMs via quantum channels.